Whole-Genome Sequencing and Genomic Variant Analysis of Kazakh Individuals - Kairov, Ulykbek; Molkenov, Askhat; Sharip, Aigul; Rakhimova, Saule; Seidualy, Madina; Rhie, Arang; Kozhamkulov, Ulan; Zhabagin, Maxat; Kim, Jong-Il; Lee, Joseph H.; Terwilliger, Joseph D.; Seo, Jeong-Sun; et al. (Frontiers in Genetics, 2022)
Kazakhstan, the ninth-largest country in the world, is located along the Great Silk Road and connects Europe with Asia. Historically, its territory has been inhabited by nomadic tribes, and modern-day Kazakhstan is a multi ethnic country with a dominant Kazakh population. We sequenced and analyzed the genomes of five ethnic Kazakhs at high coverage using the Illumina HiSeq2000 next-generation sequencing platform. The five Kazakhs yielded a total number of base pairs ranging from 87,308,581,400 to 107,526,741,301; on average, 99.06% were properly mapped. Based on the Het/Hom and Ti/Tv ratios, the quality of the genomic data ranged from 1.35 to 1.49 and from 2.07 to 2.08, respectively. Genetic variants were identified and annotated. Functional analysis of genetic variants identified several variants that were associated with higher risks of metabolic and neurogenerative diseases. The present study showed high levels of genetic admixture of Kazakhs that were comparable to those of other Central Asians. These whole genome sequence data of healthy Kazakhs could contribute significantly to biomedical studies of common diseases as their findings could allow better insight into the genotype-phenotype relations at the population level.